Silencing microRNA-27a inhibits proliferation and invasion of human osteosarcoma cells through the SFRP1-dependent Wnt/β-catenin signaling pathway. Issue 6 (4th June 2019) - Mu, Yu; Zhang, Lina; Chen, Xue; Chen, Si; Shi, Yuanyuan; Li, Junfeng
Abstract : Osteosarcoma is the most common malignant tumor of bone with a high potential for metastasis. Importantly, microRNA-27a (miR-27a) is involved in the progression of osteosarcoma. The present study aims to discuss the effects of miR-27a and its target gene secreted frizzled related protein 1 ( SFRP1 ) on proliferation and invasion of human osteosarcoma cells via Wnt/β-catenin signaling pathway. The expression of miR-27a and SFRP1 in osteosarcoma tissues and cells was detected, followed by identification of their relations. Subsequently, miR-27a mimic, miR-27a inhibitor, or siRNA against SFRP1 were introduced into cells (HOS and U2OS) to investigate their role in cell proliferation and invasion. The expression of Wnt/β-catenin signaling pathway-related gene was analyzed to further uncover the regulatory mechanism of miR-27a. The osteosarcoma tissues and cells exhibited elevated miR-27 expression and reduced SFRP1 expression. SFRP1 was verified to be a target gene of miR-27a. Meanwhile, silenced miR-27a inhibited proliferation and invasion of human osteosarcoma cells. Finally, silencing miR-27a inhibited the activation of Wnt/β-catenin signaling pathway, evidenced by reduced β-catenin expression. Our study draws a conclusion that silencing miR-27a dampens osteosarcoma progression, which might be achieved through the inactivation of the Wnt/β-catenin signaling pathway by up-regulating SFRP1.